Queen's Park Hotel, Trinidad, B.W.I. - (:unkn) unknown (My University, 2010)
The Queen's Park Hotel, located in Port of Spain on the Southern side of the Queen's Park Savannah, was first opened in January 1895. There is a taxi parked opposite to the hotel.
Colour: Black and white; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Savannas--Trinidad and Tobago; Hotels--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; [1918]; Historic buildings--Trinidad and Tobago; Historic hotels--Trinidad and Tobago; Architecture--Trinidad and Tobago; Hospitality industry--Trinidad and Tobago; Fences--Trinidad and Tobago; Automobiles--Trinidad and Tobago; Transportation--Trinidad and Tobago; Roads--Guard fences; Taxicab industry--Trinidad and Tobago; Taxicabs--Trinidad and Tobago; Queen's Park Savannah (Port of Spain)